Doppler shift simulation of scattered HF signals during the Tromsø HF pumping experiment on 16 February 1996 - T. D. Borisova; N. F. Blagoveshchenska; I. V. Moskvin; M. T. Rietveld; M. J. Kosch; B. Thidé (Annales Geophysicae, 2002)
Comparisons between bistatic scatter measurements and simulation results during the Tromsø HF pumping experiment on 16 February 1996 are made. Doppler measurements of an HF diagnostic signal scattered from the field-aligned irregularities (FAIs) in the auroral E-region were carried out on the London – Tromsø – St. Petersburg path at 9410 kHz from 21:00 to 22:00 UT. The scattered signals were observed both from natural and artificial ionospheric irregularities located in the vicinity of Tromsø. To simulate the Doppler frequency shifts, f d , of scattered signals, a radio channel model, named CONE, was developed. The model allows for ray tracing, group and phase paths, and Doppler frequency shift calculations. The calculated Doppler shifts were analyzed for dependence on the magnitude and direction of plasma velocities in the scattering volume. It was found that the velocity components in the north-south direction are crucial for explaining the Doppler frequency shifts of the scattered diagnostic signals. To simulate f d , real velocities obtained from the EISCAT UHF radar at an altitude of 278 km and from the digital all-sky imager during the experiment were employed. The simulation results of Doppler frequency shift variations with time are in reasonable agreement with the experimental Doppler shifts of scattered signals on the London – Tromsø – St. Petersburg path. Key words. Ionosphere (active experiments; ionospheric irregularities) Radio science (ionospheric propagation)